12- and 18-month follow-up after residential treatment of methamphetamine dependence: Influence of treatment drop-out and different treatment concepts. (October 2020) - Kamp, F.; Hager, L.; Proebstl, L.; Schreiber, A.; Riebschläger, M.; Neumann, S.; Straif, M.; Schacht-Jablonowsky, M.; Falkai, P.; Pogarell, O.; Manz, K.; Soyka, M.; et al.
Abstract: This study investigates the effects of two different residential treatments and of treatment drop-out in a German methamphetamine (MA) dependent sample. 108 subjects from two addiction treatment concepts were recruited at treatment begin and followed-up at 12 (T2) and 18 (T3) months after treatment. Based on follow-up samples (n = 38 at T2, n = 25 at T3), 77.1% at T2 and 68.0% at T3 were MA abstinent. Classifying everyone, who did not participate at follow-ups as having had a relapse, showed MA-abstinence rates of 25.0% (at T2) and 15.7% (at T3). There was no difference in MA-use between treatment conditions nor between treatment completers and drop-outs. Having injected any substance predicted MA-use at T2 (p = .03). The median time of relapse was 1.5 days after hospital release. Depression scores at T2 predicted MA-use at T3 (p = .02). T2 participants that dropped out of treatment had higher craving scores at T2, than T2 subjects who completed treatment (p = .03). The results show positive effects of current inpatient treatment programs without differences between different concepts. More research is needed to clarify the impact of treatment drop-out. Attention should be paid to a successful transition from residential to outpatient services and to a reduction of study attrition.